2015
DOI: 10.9734/indj/2015/12118
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study and Review: Physiological Differences in BDNF, a Potential Biomarker in Males and Females with Autistic Disorder

Abstract: Aims There is a need for more biologic research in autistic disorder (AD) to determine if biomarkers exist that would be useful for correlating to symptom severity and/or clinical improvement during treatment. Given the fact that AD is 4 times more common in males than females, gender differences in physiological biomarkers may be present. One potential biomarker that has begun to be studied is brain-derived neurotropic factor (BDNF), a peptide involved in the regulation of neuronal cell survival, differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…After reading the titles and abstracts, 28 appropriate articles were identified for full-text analysis. We scrutinized the 28 articles and excluded 9 articles for lack of necessary data on BDNF levels, patient samples that overlapped with another study, adult study participants, data reporting BDNF messenger RNA levels, and no data reported on healthy controls . Thus, 19 studies with 2896 unique participants met criteria for inclusion in the present meta-analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 95%
“…After reading the titles and abstracts, 28 appropriate articles were identified for full-text analysis. We scrutinized the 28 articles and excluded 9 articles for lack of necessary data on BDNF levels, patient samples that overlapped with another study, adult study participants, data reporting BDNF messenger RNA levels, and no data reported on healthy controls . Thus, 19 studies with 2896 unique participants met criteria for inclusion in the present meta-analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 95%
“…After scanning the titles and abstracts, 62 articles relevant to present subject were identified for full-text scrutiny. Several studies were excluded as they did not have necessary data (11 studies) [20][21][22][23][24][25][26][27][28][29][30] ; lack of healthy controls (6 studies) [31][32][33][34][35][36] ; sample source is not peripheral blood (5 studies) 18,[37][38][39][40] ; samples derived from postmortem brain (3 studies) 10,11,41 ; participants were adults (3 study) 16,42,43 ; had patient samples that overlapped with another studies (1 study) 44 ; neurotrophic factors were studied in less than 3 articles (1 study) 19 and non-English publication (1 studies) 45 . Therefore, a total of 31 studies met the criteria were included for this meta-analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When TSH was studied on the MSD platform, again, the ASD boys had an average 30% lower level vs. TD boys. We limited our study to boys because several studies report sex-specific differences in putative ASD biomarkers [ 15 , 26 , 27 ], and we only had access to a small sample of ASD and TD girls.…”
Section: Discussionmentioning
confidence: 99%